Effects of pentoxifylline on exercising skeletal muscle vascular control in rats with chronic heart failure - Rico, Gabrielle (Kansas State University, 2013)
Both cardiac and peripheral vasculature dysfunction likely contribute, in part, to elevations in TNF-[alpha] and exercise intolerance in chronic heart failure (CHF). The pharmaceutical TNF-[alpha] synthesis suppressor pentoxifylline (PTX) reduces plasma [TNF-[alpha]] and improves left ventricular (LV) function in CHF rats, but the effects of PTX on skeletal muscle blood flow (BF) and vascular conductance (VC) during exercise are unknown. We tested the hypothesis that PTX would elevate skeletal muscle BF and VC at rest and during submaximal treadmill exercise in CHF rats (coronary artery ligation). CHF rats received i.p. injections of 30 mg·kg[superscript]-[superscript]1·day[superscript]-[superscript]1 of PTX (CHF+PTX, n=13) or saline (CHF, n=8) for 21 days. Mean arterial pressure (MAP) and BF (radiolabeled microsphere infusions) were measured at rest and during treadmill exercise (20 m/min, 5% grade). Myocardial infarct (MI) size was not different between groups (CHF: 37±4, CHF+PTX: 37±3% of LV wall; p>0.05). Resting and exercising MAP was greater in CHF+PTX compared to CHF (p<0.05 for both). At rest, total hindlimb skeletal muscle BF and VC were not different between groups (p>0.05). However, during exercise PTX increased total hindlimb BF (CHF: 83±9, CHF+PTX: 114±8 ml·min[superscript]-[superscript]1·100g[superscript]-[superscript]1, p<0.05) and VC (CHF: 0.75±0.08, CHF+PTX: 0.88±0.06 ml·min[superscript]-[superscript]1·100g[superscript]-[superscript]1·mmHg[superscript]-[superscript]1, p<0.05). Furthermore, exercising BF was increased in 21, and VC in 11, of the 28 individual hindlimb muscles or muscle parts with no apparent fiber-type specificity. Thus, PTX administration augments skeletal muscle BF and VC during locomotory exercise in CHF rats, which carries important therapeutic implications for CHF patients.
Keywords: Myocardial infarction; Blood flow; TNF-alpha; Oxygen delivery; Vasodilation; Pentoxifylline; Kinesiology (0575)